Kerentaan Penduduk Usia Lanjut Di Jawa - Bali - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Abstract Most elderly have lower education level, they work in agriculture with lower income so it is natural if they are categorized as vulnerable in meeting their basic needs. They are willing to work anything, they depend on the fund giving by their children and children in law as long as they have income. This depency is higher on elderly women than men. When they get stick, they only go to puskesmas or pustu to find the cure. They spend most of their time watching television even most of the program are not suitable to their needs. The goverment has done many programs in helping there vulnerable citizens, but still these elderly have not catch their attention yet.